A geração que não deve ser esquecida: a construção da memória estudantil cearense na resistência à Ditadura Civil-militar - Oliveira Filho, José Ivan de (2017)
The process of political openness in the late 1970s was negotiated and conducted by the military in order to avoid friction and permit political accommodation. The Lei da Anistia in 1979 imposed the "forgetfulness" model, treating crimes of regime agents as justifiable, calling them "related crimes." Brazil did not carry out an examination of the past soon after the end of the dictatorial period, limiting itself to the cash restitution of the regime's victims and an apology, treating the issue as of the private sphere. In 2011, the presidency sanctioned Law 12.528, which regulated the Comissão Nacional da Verdade (CNV), the ultimate effort to overcome "forgetfulness". This master's thesis has as its starting point the participation in the Comissão da Verdade das Universidades do Estado do Ceará, which occurred during March and June of 2014 and was part of the official unveiling movement of the past proposed by the CNV. A total of 28 testimonies were heard, which are the basis for the present study, which also invested in memoirs, documentaries and other records. We seek to analyse memory as a composition inserted in a field of dispute for acknowledgment (Michel Pollak and Axel Honneth), permeated by subjective and interpersonal negotiations. Memory is a central component in the construction of one's identity, which is related to belonging to certain groups. In this sense, the memory of our informants composes what we call a "memory community": an identity sustained by generational identification (Mannhein) and sharing of common memories (Halbwachs). We work with three categories of memory: the nostalgia, which refers to good memories and stories that reinforce and value group identity; the denunciation, which registers the barbarity of the state of exception and has the duty to count on the other forms of violence and offence; finally, the self-criticism, which problematises the system of moral charges and overvaluation of one's own capacities.